Towards Inclusive and Resilient Living Environments for Older Adults: A Methodological Framework for Assessment of Social Sustainability in Nursing Homes - Vanja Skalicky Klemenčič; Vesna Žegarac Leskovar (Buildings, 2025)
The quality of living environments for older adults represents a critical component of social sustainability in an ageing society. Among various housing options, nursing homes are the most institutionalised form of elderly care and demand special attention regarding architectural design. This paper explores the impact of architectural and open space features on social sustainability in living environments for older adults. A comparative analysis of three Slovenian nursing homes is presented. The first two, built in the post-war period, were based on elevated architectural criteria inspired by Swedish human-centred housing design. The third was completed in 2021 in the post-COVID-19 era, which revealed the vulnerability of such housing typologies. An integrated methodological framework was developed by applying two complementary assessment tools: the Safe and Connected, developed by the authors to evaluate the spatial, health, and social resilience of nursing home environments, and the Well-being and Integration, addressing the role of open space with a particular emphasis on the identification of older adults with their environment and the facilitation of social resilience. Both tools evaluate indicators linked to the social dimension of quality of life for older adults. The results show a gradual improvement in architectural quality from the 1960s to the 1980s, followed by a partial decline in the contemporary case. The Swedish example scored highest across both tools. In contrast, the newest Slovenian facility scored surprisingly low in social integration, highlighting critical gaps in current nursing home design. This study demonstrates the value of applying interdisciplinary, tool-based evaluations in identifying design strategies that foster resilient and inclusive LTC environments, and the proposed framework may serve as a decision-making aid for architects, planners, and policymakers. This research highlights the importance of reintroducing human-oriented design principles to support socially sustainable nursing home environments.